2016
DOI: 10.1002/ps.4430
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of Myrtaceae plant essential oils and their major components againstDrosophila suzukii(Diptera: Drosophilidae)

Abstract: Myrtaceae plant EOs and their components have an excellent potential for being used in the control of SWD adults and could be useful in the development of more effective natural compounds as alternatives to synthetic pesticides. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 38 publications
6
33
0
Order By: Relevance
“…In agreement with our results, Jang et al [48] found that the major EOs constitutes of C. citriodora are α-citronellal and isopulegol. Singh et al [26] found that the major monoterpenoids detected in the EO of C. citriodora were citronellal (60.6%), β -citronellol (12.5%), and isopulegol (8.1%).…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with our results, Jang et al [48] found that the major EOs constitutes of C. citriodora are α-citronellal and isopulegol. Singh et al [26] found that the major monoterpenoids detected in the EO of C. citriodora were citronellal (60.6%), β -citronellol (12.5%), and isopulegol (8.1%).…”
Section: Discussionsupporting
confidence: 94%
“…These results show the potential of the use of this compound for the control of the A. aegypti mosquito. Our results corroborate those of previous studies that have shown that EOs from plants have an efficient insecticidal action on several pests . However, few studies have evaluated the potential insecticidal and sublethal effects of these compounds on populations of resistant insects, including A. aegypti .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported that the main compounds of the EOs of C. citriodora leaves were α-citronellal and isopulegol [46]; citronellal, β-citronellol, and isopulegol [23]; citronellal and β-citronellol [28]; β-citronellal in plants grown in Brazil [47]. Citronellal, citronellol, Neo-isopulegol, E-caryophyllene, iso-isopulegol, and citronellyl acetate were found as the main compounds in the EO of C. citriodora from Benin [48]; α-citronellal, citronellol acetate, α-citronellol, and isopulegol were also the main compounds [20]; α-pinene and 1.8-cineole the main compounds in the plant grown in Tunisia [30].…”
Section: Discussionmentioning
confidence: 97%